Neural analysis of elastoplastic plane stress problem with unilateral constraints - Pabisek, Ewa (Computer Assisted Methods in Engineering and Science; Vol 14 No 3 (2007), 2022)
The paper is a development and continuation of paper [8] where the Panagiotopoulos approach was extended for the elastoplastic analysis. In case of elastic analysis the parameters of the Hopfield-Tank Neural Network (HTNN) are calibrated only once but the updating of the elastoplastic stiffness matrix needs an iteration of HTNN and FE system. The main problem is the matrix condensation repeated for each iteration step of the Newton-Raphson method. Besides all the improvements proposed in [15], a new interacting program has been implemented which enables a significant decrease of the processing time (number of iterations) in comparison with the time achieved in [8]. The results of the extensive numerical analysis are discussed for a tension perforated strip with a rigid bolt placed frictionlessly in a circular hole in the middle of the strip.